IDENTIFIKASI JENIS MAKROALGA COKELAT (PHAEOPHYTA) DI PERAIRAN PANTAI BLUE MERLIN, TELUK TOMINI, GORONTALO - Sridamayani, Ni Wayan; Nane, La (Biospecies, 2022)
Macroalgae have an important role in the coastal environment and human beings. Unfortunately, the research on species identification of macroalgae is very poor. On the other hand, data collection of macroalgae is essential to be used for effectiveness in conservation efforts for coastal ecosystem resources. Thereby, the identification of macroalgae is needed, particularly for brown algae as the database that can be used in the management of coastal resources in Tomini Bay. This research was conducted for 45 days, from November 15 to December 29, 2020, in the Blue Marlin Beach, Tomini Bay, Gorontalo City. GPS coordinate, sea current, seawater temperature, and waves were measured with Fishing Points Software. Sample collection was performed by a search method. Each specimen that was found was kept in a plastic zipper bag and stored in a coolbox containing an ice-cube to maintain the fresh sample. After collection, the specimens were carried out to the laboratory for identification and measurement as soon as possible. The results show three brown algae species in the Blue marlin Beach, i.e., Padina australis, Turbenaria decurrens, and Sargassum polycystum. The average of seawater temperature, sea current, and waves during the study is 31 C, 0.1 m/s, and 0,2 m, respectively.